Compliment Expression Found in Whiplash Movie by Damien Chazelle: Pragmatics Study - Dhiya Zhafira Phrasajid Putri; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research analyzed the speech act of compliment expression and function of compliment expression found in the movie Whiplash. The purpose of this study is to analyzed the various types of compliment words and function of compliment expression. To analyze this research is a qualitative descriptive. The data source from Damien Chazelle’s movie script and the film. Based on the findings there are 5 types of compliment words appearance (25%), possessions (12,5%), personality, (12,5%), ability (12,5%), achievement (37,5%). In addition, there are three function of compliment expression: to express admiration (62,5%), to create solidarity (25%), to soften threat (12,5%).